Bone marrow aspiration in north Sudan: the procedure, indications and the diagnostic value - Elmadhoun, Wadie M; Noor, Sufian K; Bushara, Sarra O; Almobarak, Ahmed O; Husain, Nazik Elmalaika; Ahmed, Mohamed H (International Journal of Health Sciences, 2015)
Introduction: Bone marrow aspiration (BMA) is a common and useful investigation tool in clinical practice to obtain information about both hematological and non-hematological disorders. The aim of the work was to identify the main indications for BMA in Atbara city, north Sudan and to determine the common diagnoses encountered. Methods: All reports of BMA carried out during a 6-year period from 2009 to 2014, in the Modern Specialized Laboratory (the only site where BMA is conducted in Atbara) were reviewed. The information extracted included the main indications for performing this procedure, age groups involved, and the most common diagnoses established. A specially designed form was used for this purpose and the data were analyzed using SPSS computer program. Results: A total number of 112 cases were subjected to bone marrow aspiration. The most frequent indications were: pancytopenia 43(38.4%), anemia 39 (34.8%), and suspected leukemia 13 (11.6%).In 86(76.8%) cases, BMA provided either the diagnosis or diagnostic clues to the disease process, while 26 (23.2%) of the aspirates revealed a normally functioning marrow. Conclusion: Bone marrow aspiration is an important investigation for establishing the diagnosis in many medical conditions. The most common indication for this procedure in our study was pancytopenia and the most common finding was aplastic anemia. Â 